Inhibition, emotional self-control, working memory, and monitoring. Do they predict the typical manifestations of adults with ADHD? - Belén Roselló; Carmen Berenguer; Inmaculada Baixauli (INFAD, 2019)
Introduction. Deficits in inhibition, emotional control, working memory and monitoring have been evidenced in numerous investigations focused on attention déficit hyperactivity disorder (ADHD), but information about its posible differential influence on the characteristic manifestations of the disorder is not very well known. Objectives.The purpose of this study was to analyze the relationships and the predictive power of the regulation functions (inhibition and emotional control) and metacognitive functions (working memory and supervisión) in the manifestations of ADHD. Method. Sixty-one Young adults between the ages of 18 and 24 with a combined clinical diagnosis of ADHD subtype in childhood completed the Conners Scale of ADHD Symptoms and the Executive Performance Inventory (BRIEF). Results. Statistically significant relationships were found between inhibition, emotional regulation, working memory and monitoring and the Conners subscales. In addittion, deficits in executive functions were diferentially sensitive in predicting significant ADHD problems. Working memory and supervisión were predictors of attention problems, inhibition prediced self-concept problems and hyperactivity/restlessness while emotional self-control was the best predictor of impulsivity. Conclusions. The assessment of behavioral regulation functions and metacognitive executive functions may assist both in the diagnosis and the follow-up evaluations of treatment of adults with ADHD.